Making Heritage Through Montana's Official State Highway Maps, 1914–2000*. Issue 3 (2nd July 2020) - Briwa, Robert; Wyckoff, William
Abstract: We assess Montana highway maps produced between 1914 and 2000 to identify how the Montana Department of Transportation and its predecessors used maps to frame Montana's place identity and heritage for promotional purposes in the twentieth century. After 1934, we document how Montana's official state maps became a key source and shaper of tourist knowledge about the state, its history, and its attractions. Five persistent map themes—territorial identity, mythic West, natural wealth, outdoor recreation, and hospitality—are used to define Montana landscapes and heritage and to shape perceptions of the state. The normative and persuasive powers of Montana highway maps reveal them as premiere examples of a portable and place‐defining affective technology used to promote tourism within the twentieth‐century American West.